Thermal Analysis of Preparation of Hydroxyapatite-Ca(NO3)2 and Na3PO4 Mixture Reaction Solution Based on Numerical Simulation - Xu, Chen; Jun, Shu; Yang, XiaoQing; Huang, KaMa; Liu, Pukun (Asian Journal of Chemistry, 2012)
A numerical model was presented to study the temperature distribution during the heterogeneous mixture reaction solution under microwave radiation. A case study of the preparation of hydroxyapatite, the electromagnetic field equations, fluid dynamics equations and heat transfer equations were solved by using finite-element method. The calculated results are in agreement with the experiments. The results show that the location of the hot spots is related to time and the hot spots often exist near the interfaces between the solution, solid and air.